The Parturient With Implanted Spinal Cord Stimulator: Management and Review of the Literature. Issue 1 (March 2016) - Young, A.C.; Lubenow, T.R.; Buvanendran, A.
Abstract : ( Reg Anesth Pain Med. 2015;40:276–283) Women with complex regional pain syndrome can be effectively treated using an implanted spinal cord stimulator, when conservative treatment proves ineffective. This could allow women to stop using potentially harmful analgesic medications during pregnancy.